1981
DOI: 10.1111/j.1432-1033.1981.tb05330.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Arginine Residues in Porcine Pancreatic Phospholipase A2

Abstract: Although phenylglyoxal monohydrate reacts with Arg-6 in porcine pancreatic phospholipase Az, concomittantly the a-amino group of the N-terminal Ala-1 residue is quantitatively transaminated. Due to this latter reaction the enzymatic activity toward micellar substrate is lost irrespective of the Arg-6 modification. Upon reaction of [7-'4C]phenylglyoxal monohydrate with a-amino-blocked phospholipase Az analogs, two molecules of the reagent were incorporated per protein molecule, which were found to be present on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Ca 2+ is essential for both catalysis and binding of some enzymes to the substrate [26]. A study of Ca 2+ requirement in primary screwworm PLA 2 preparations showed that the enzyme activity was almost abolished in the presence of calcium chelator, EGTA.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ is essential for both catalysis and binding of some enzymes to the substrate [26]. A study of Ca 2+ requirement in primary screwworm PLA 2 preparations showed that the enzyme activity was almost abolished in the presence of calcium chelator, EGTA.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that Ca 2+ is essential for both, catalysis and enzyme binding to the substrate [40-42]. In order to investigate the effect of Ca 2+ on ChPLA 2 -IIA activity, we studied the variation of hydrolysis rates of egg yolk phospholipids by pure ChPLA 2 -IIA in the presence of various Ca 2+ concentrations (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…This mixture was stirred for 2 h at 25 °C (covered with aluminum foil), then frozen and dried as before. Arginine blocking of ISP was accomplished by treating freshly purified ISP with phenylglyoxal (Vallejos and others 1978; Fleer and others 1981). A portion of the neutralized ISP slurry (pH 7.0) corresponding to ca.…”
Section: Methodsmentioning
confidence: 99%